2019
DOI: 10.1108/ecam-02-2019-0073
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for implementing integrated construction project delivery

Abstract: Purpose The purpose of this paper is to identify the critical success factors (CSFs) to implement integrated project delivery (IPD) systems in the Korean construction industry. Design/methodology/approach This study categorized potential CSFs and analyzed them using factor analysis and multiple regression analysis to choose the best ones based on responses from Korean construction experts. Findings In total, 29 potential factors were selected and categorized into 7 CSFs using factor analysis. Originality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 12 publications
3
23
0
1
Order By: Relevance
“…Neste sentido, destaca-se a necessidade do alinhamento conceitual dos elementos do IPD, e a relação de abrangência entre eles (MOLLAOGLU-KORKMAZ; MILLER; SUN, 2014;OSBURN et al, 2018). Além disso, os reais benefícios do IPD em prática ainda são pouco compreendidos na indústria da construção civil (DE MARCO;KARZOUNA, 2018;WHANG;KIM, 2019;TENG et al, 2019). Os limites de conhecimento e aplicabilidade do IPD têm dissuadido a adoção dos seus elementos em ambientes de produção de empreendimentos com pouca experiência com esta prática (LAURENT; LEICHT, 2019;ABDIRAD;DOSSICK, 2019;DURDYEV et al, 2019).…”
Section: Gestão and Tecnologia De Projetosunclassified
“…Neste sentido, destaca-se a necessidade do alinhamento conceitual dos elementos do IPD, e a relação de abrangência entre eles (MOLLAOGLU-KORKMAZ; MILLER; SUN, 2014;OSBURN et al, 2018). Além disso, os reais benefícios do IPD em prática ainda são pouco compreendidos na indústria da construção civil (DE MARCO;KARZOUNA, 2018;WHANG;KIM, 2019;TENG et al, 2019). Os limites de conhecimento e aplicabilidade do IPD têm dissuadido a adoção dos seus elementos em ambientes de produção de empreendimentos com pouca experiência com esta prática (LAURENT; LEICHT, 2019;ABDIRAD;DOSSICK, 2019;DURDYEV et al, 2019).…”
Section: Gestão and Tecnologia De Projetosunclassified
“…Through reviewing previous studies, this study identified a preliminary list of 47 potential project success factors, which were initially grouped into four main categories: project characteristics (e.g. Chen et al , 2012; Cserháti and Szabó, 2014; Dang and Le-Hoai, 2016; Banihashemi et al , 2017; Wang et al , 2018; Whang et al , 2019), socioeconomic factors (e.g. Li et al , 2005; Tang et al , 2012; Yu and Shen, 2015; Banihashemi et al , 2017; Wang et al , 2018; Whang et al , 2019), sustainability-related factors (e.g.…”
Section: Identification Of Critical Success Factors For Coastal Urban Projectsmentioning
confidence: 99%
“…Chen et al , 2012; Cserháti and Szabó, 2014; Dang and Le-Hoai, 2016; Banihashemi et al , 2017; Wang et al , 2018; Whang et al , 2019), socioeconomic factors (e.g. Li et al , 2005; Tang et al , 2012; Yu and Shen, 2015; Banihashemi et al , 2017; Wang et al , 2018; Whang et al , 2019), sustainability-related factors (e.g. Kamphuis, 2011; Xiao et al , 2015; Yalegama et al , 2016; Banihashemi et al , 2017; Oh et al , 2018; Whang et al , 2019) and participant-related factors (e.g.…”
Section: Identification Of Critical Success Factors For Coastal Urban Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSFs have been studied by many researchers in the construction sector (Whang et al, 2019, Maghsoodi and Khalilzadeh, 2018, and Gunduz and Yahya, 2018. Building contractors' efficiency has also been investigated by various researchers.…”
Section: Literature Review and Selection Of Csfsmentioning
confidence: 99%